2015
DOI: 10.3389/fpsyg.2015.01656
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the optimal viewing position effect in Chinese

Abstract: Substantial evidence indicates that where readers fixate within a word affects the efficiency with which that word is recognized. Indeed, words in alphabetic languages (e.g., English, French) are recognized most efficiently when fixated at their optimal viewing position (OVP), which is near the word center. However, little is known about the effects of fixation location on word recognition in non-alphabetic languages, such as Chinese. Moreover, studies to date have not investigated if effects of fixation locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
3
3
0
Order By: Relevance
“…Importantly, the present study ruled out the possibility that the different effects of inserting a space before and after a word are caused by landing position effects. The results that gaze duration was longer when the eyes fixated on the first character than on the second character within a word in the space after the word condition are completely inconsistent with the OVP effects (P. Liu & Li, ; P. Liu et al, ). The present results may be due to information density because there was a space after the second character within a word.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, the present study ruled out the possibility that the different effects of inserting a space before and after a word are caused by landing position effects. The results that gaze duration was longer when the eyes fixated on the first character than on the second character within a word in the space after the word condition are completely inconsistent with the OVP effects (P. Liu & Li, ; P. Liu et al, ). The present results may be due to information density because there was a space after the second character within a word.…”
Section: Discussionsupporting
confidence: 93%
“…The study by P. Liu and Li () reported that readers initially tended to fixate on the first character (e.g., 呼 ) in the space after word condition (e.g., 呼 吁 ) and on the second character (e.g., 吁 ) in the space before word condition (e.g., 呼 吁 ). Previous studies of optimal viewing position (OVP) have also indicated that Chinese word recognition is most efficient when the eyes fixate more on the first character (i.e., OVP) than on the second character of a two‐character for both words and nonwords (P. Liu & Li, ; P. Liu, Liu, Han & Paterson, ). Therefore, the shorter reading time in the space after compared with the space before condition might be explained by initial fixations being more likely to be located at the OVP in the space after word condition.…”
Section: List Of Possible Facilitatory and Inhibitory Effects Of Spacmentioning
confidence: 99%
“…This adds to the growing evidence that old readers suffer from greater reading difficulties (Kemper, Crow & Kemtes, 2004; Kliegl et al, 2004; Stine-Morrow, Miller & Herzog, 2006; Rayner et al, 2006; Rayner, Castelhano & Yang, 2009; Laubrock, Kliegl & Engbert, 2006). We also found some age changes that are specific of Chinese, that is, compared to reading alphabetic languages such as English and German, old adults reading Chinese employ a more cautious eye movement strategy (i.e., they skip words less frequently), which is consistent with previous studies (Liu et al, 2015; Wang et al, 2016; Zang et al, 2016). These researchers proposed that increased difficulty in processing word boundary in the preview phase with age causes older adult readers to use a more careful reading strategy to compensate for this difficulty.…”
Section: Discussionsupporting
confidence: 91%
“…This adds to the growing evidence that old readers suffer from greater reading difficulties (Kemper et al, 2004;Kliegl et al, 2004;Stine-Morrow et al, 2006;Rayner et al, 2006Rayner et al, , 2009Laubrock et al, 2006). We also found some age changes that are specific of Chinese, that is, compared to reading alphabetic languages such as English and German, old adults reading Chinese employ a more cautious eye movement strategy (i.e., they skip words less frequently), which is consistent with previous studies (Liu, Liu, Han, & Paterson, 2015;Wang et al, 2016;Zang et al, 2016). These researchers proposed that increased difficulty in processing word boundary in the preview phase with age causes older adult readers to use a more careful reading strategy to compensate for this difficulty.…”
Section: Comparison Between Experimentssupporting
confidence: 91%